MicroRNAs in spermatogenesis dysfunction and male infertility: clinical phenotypes, mechanisms and potential diagnostic biomarkers - Shi, Ziyan; Yu, Miao; Guo, Tingchao; Sui, Yu; Tian, Zhiying; Ni, Xiang; Chen, Xinren; Jiang, Miao; Jiang, Jingyi; Lu, Yongping; Lin, Meina (Frontiers in Endocrinology, 2024)
Infertility affects approximately 10–15% of couples worldwide who are attempting to conceive, with male infertility accounting for 50% of infertility cases. Male infertility is related to various factors such as hormone imbalance, urogenital diseases, environmental factors, and genetic factors. Owing to its relationship with genetic factors, male infertility cannot be diagnosed through routine examination in most cases, and is clinically called ‘idiopathic male infertility.’ Recent studies have provided evidence that microRNAs (miRNAs) are expressed in a cell-or stage-specific manner during spermatogenesis. This review focuses on the role of miRNAs in male infertility and spermatogenesis. Data were collected from published studies that investigated the effects of miRNAs on spermatogenesis, sperm quality and quantity, fertilization, embryo development, and assisted reproductive technology (ART) outcomes. Based on the findings of these studies, we summarize the targets of miRNAs and the resulting functional effects that occur due to changes in miRNA expression at various stages of spermatogenesis, including undifferentiated and differentiating spermatogonia, spermatocytes, spermatids, and Sertoli cells (SCs). In addition, we discuss potential markers for diagnosing male infertility and predicting the varicocele grade, surgical outcomes, ART outcomes, and sperm retrieval rates in patients with non-obstructive azoospermia (NOA).